Chip-based human liver–intestine and liver–skin co-cultures – A first step toward systemic repeated dose substance testing in vitro - Maschmeyer, Ilka; Hasenberg, Tobias; Jaenicke, Annika; Lindner, Marcus; Lorenz, Alexandra Katharina; Zech, Julie; Garbe, Leif-Alexander; Sonntag, Frank; Hayden, Patrick; Ayehunie, Seyoum; Lauster, Roland; Marx, Uwe; et al. (European journal of pharmaceutics and biopharmaceutics, 2015)
[Display omitted] •The MOC allows integration of biological barriers into dynamic multi-tissue systems.•A human primary intestinal and a liver model were combined in a microfluidic system.•Liver and skin models were co-cultured in endothelialized multi-organ-chips.•Oral treatment of co-cultures was modeled by apical application to intestinal tissue. Systemic repeated dose safety assessment and systemic efficacy evaluation of substances are currently carried out on laboratory animals and in humans due to the lack of predictive alternatives. Relevant international regulations, such as OECD and ICH guidelines, demand long-term testing and oral, dermal, inhalation, and systemic exposure routes for such evaluations. So-called “human-on-a-chip” concepts are aiming to replace respective animals and humans in substance evaluation with miniaturized functional human organisms. The major technical hurdle toward success in this field is the life-like combination of human barrier organ models, such as intestine, lung or skin, with parenchymal organ equivalents, such as liver, at the smallest biologically acceptable scale. Here, we report on a reproducible homeostatic long-term co-culture of human liver equivalents with either a reconstructed human intestinal barrier model or a human skin biopsy applying a microphysiological system. We used a multi-organ chip (MOC) platform, which provides pulsatile fluid flow within physiological ranges at low media-to-tissue ratios. The MOC supports submerse cultivation of an intact intestinal barrier model and an air–liquid interface for the skin model during their co-culture with the liver equivalents respectively at 1/100.000 the scale of their human counterparts in vivo. To increase the degree of organismal emulation, microfluidic channels of the liver–skin co-culture could be successfully covered with human endothelial cells, thus mimicking human vasculature, for the first time. Finally, exposure routes emulating oral and systemic administration in humans have been qualified by applying a repeated dose administration of a model substance – troglitazone – to the chip-based co-cultures.